MENINGKATKAN HASIL BELAJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI MAN 1 LABUHANBATU - Witma Novita Atnur; Erlia Utami Panjaitan; Syahraini Syahraini; Samsir Samsir (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
As for the background of the research on the results of direct observations at MAN 1 Labuhanbatu, the learning outcomes of cell material biology were disappointing. The research aims to see the effect of the Problem Based Learning Model on the Improvement of Biology Learning Outcomes for class XI students. The research was conducted at MAN 1 Labuhanbatu. The study population was 35 class XI students. They were using classroom action research methods, referring to Kemmis and Taggart design models. In the initial test, the mean score was 28.57%. In the first test, it increased 62.86%. The second stage increased, the mean of the second result was found to increase to 85.71%, an increase of 22.85% from the first stage test. The improvement of student learning outcomes in class XI MAN 1 Labuhanbatu in Biology Lessons with cell material ≥ 75% was successfully achieved. So that it can be concluded that the Problem Based Learning model can make the learning outcomes of students in class XI MAN 1 Labuhanbatu in Biology Lessons with cell material increase significantly.